ANALISIS KEPUASAN PENGUNJUNG KAWASAN WISATA LEMBAH HARAU KABUPATEN LIMAPULUH KOTA - Regi Indah Kemala Sari; Latifa Hanum; Raeza Firsta Wirsa (Universitas Sebelas Maret, 2020)
The purposes of this study are (1) analyze the level of visitor satisfaction with the dimensions of quality (physical, reliability, responsiveness, assurance, and empathy) in the Harau Valley Tourism Area (HVTA), (2) analyze priorities for improving service quality (physical, reliability, power responsiveness, guarantees, and empathy) HVTA. The study was conducted in the Harau Valley Tourism Area, Limapuluh Kota Regency. The research sample of 100 respondents were selected using accidental sampling technique. Data were analyzed descriptively quantitatively using the IPA (Importance Performance Analysis) and CSI (Customer satisfaction Index) methods. The study was conducted in August 2019 until November 2019. The results showed that the level of satisfaction of HVTA visitors by 69% meant that visitors were satisfied with the attributes in HVTA. The attributes of natural beauty are the attributes with the highest level of importance and satisfaction, each at 4.29 and 4.39, while the ticket price is the attribute with the lowest level of importance and satisfaction at 3.26 and 2.78, respectively.